2001
DOI: 10.1111/j.1748-720x.2001.tb00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Five Years afterQuinlan: A Review of the Jurisprudence of Death and Dying

Abstract: Ever since the 1960s, when medical science became capable of prolonging the dying process beyond bounds that many patients would find acceptable, people have sought “death with dignity,” or “a natural death,” or “a good death.” Once debilitation from a fatal affliction has reached a personally intolerable point, dying patients have sought to control the manner and timing of death via diverse techniques. Some sought the disconnection of life-sustaining medical interventions, such as respirators and dialysis mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Despite a number of state courts in the USA echoed Quinlan and Cruzan on the patient's prerogative to refuse treatment[51], the recent case of Theresa Marie (Terri) Schiavo seemed to call into question past legal and ethical consensuses[52]. In 1990, Theresa Marie (Terri) Schiavo, 26 years of age, had a cardiac arrest and experienced severe hypoxia for several minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a number of state courts in the USA echoed Quinlan and Cruzan on the patient's prerogative to refuse treatment[51], the recent case of Theresa Marie (Terri) Schiavo seemed to call into question past legal and ethical consensuses[52]. In 1990, Theresa Marie (Terri) Schiavo, 26 years of age, had a cardiac arrest and experienced severe hypoxia for several minutes.…”
Section: Discussionmentioning
confidence: 99%
“…As indications for their use expand, clinicians will encounter more requests for their withdrawal near the end of life. Despite a clear ethical and legal precedent regarding the cessation of life-sustaining therapies, [1][2][3][4] there is still considerable controversy surrounding the withdrawal of pacemakers. We describe the case of a terminally ill, pacemaker-dependent patient who requested to have her pacemaker turned off near the end of life.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1970s, the ability of competent individuals to control medical interventions led to support for advance directives that enabled individuals, either through living wills or health care proxies, to express their values and preferences about medical treatment when they would no longer be competent to make decisions. In the landmark case in re Quinlan , the New Jersey Supreme Court found that “Karen’s choice [to decline medical treatment], if she were competent to make it, would be vindicated by the law” and “should not be discarded solely because her condition prevents her conscious exercise of the choice.”…”
Section: Essaymentioning
confidence: 99%